Strategi Badan Usaha Milik Desa “Amanah” Dalam Pengelolaan Wisata Di Era Digital - Sudarman, Sudarman; Sinrang, Andi; Erfina, Erfina (Universitas Muhammadiyah Mataram, 2025)
This research aims to analyze the strategy of Village-Owned Enterprises (BUMDes) Amanah in managing Pattumba Waterfall tourism in the digital era. A phenomenological qualitative approach was used to provide an in-depth description of the role of the Local Government and BUMDes in the management of this tourist attraction. Data were obtained through direct observation, structured interviews with various stakeholders, and related documentation. Data were analyzed using Nvivo 12 Plus software to support thematic analysis and identify important patterns. The research findings show that advances in Information and Communication Technology (ICT) have contributed significantly to tourism promotion and management through digital platforms such as social media and online ticket reservation systems. The use of digital technology has helped improve the efficiency of recording visitor information and managing daily operations. However, challenges such as the lack of adequate infrastructure and the low digital literacy of the local community still pose obstacles. The implication of this research is that proper utilization of ICT can increase the visibility and attractiveness of tourist destinations, as well as support more efficient management. The original value of this research lies in the in-depth analysis of the role of BUMDes Amanah and the use of digital technology in tourism management, which can serve as a reference for the development of similar strategies in other areas.